Chemical Constituents and Antifungal Properties of Piper ceanothifolium Kunth Against Phytopathogens Associated with Cocoa Crops - Yudy S. Mahecha-Jimenez; Oscar J. Patiño-Ladino; Juliet A. Prieto-Rodríguez (Plants)
In this study, the antifungal potential of chemical constituents of Piper ceanothifolium Kunth was determined against three phytopathogenic fungi associated with the cocoa crop. The methodology included the phytochemical study of the inflorescences of P. ceanothifolium, the synthesis of a chroman-4-one type derivative and the evaluation of the antifungal activity against Moniliophthora roreri, Fusarium solani, and Lasiodiplodia theobromae. The phytochemical study led to the isolation and identification of two new hydroquinones (1 and 5), together with three known compounds (hydroquinones 2 and 3, and chromene 4). The synthesis of a new chromone 6 obtained from 2 through an oxa-Michael type intramolecular cyclization is also reported. All compounds showed strong antifungal activity, with 6 (IC50 of 16.9 µM) standing out for its action against F. solani, while prenylated hydroquinones 1 (30.4 µM) and 2 (60.0 µM) were the most active against M. roreri and L. theobromae, respectively. The results of this research represent the first report of the chemical composition and antifungal properties for P. ceanotifolium, suggesting its potential use as a control method against M. roreri, F. solani, and L. theobromae.